2015
DOI: 10.1179/1743132815y.0000000013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of virtual reality-based balance training in multiple sclerosis

Abstract: According to the fall risk and postural stability tests results, the VR-based balance training program could improve the balance ability of the patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 35 publications
1
60
0
1
Order By: Relevance
“…Balance/rebalancing, postural stability and weight-shifting exercises with and without visual feedback were administered using a balance platform (Biodex Medical Systems, Inc., Shirley, NY) that had been tested previously in multiple sclerosis patients [27]. Each task was trained for about 2 min, and the patients were provided with a rest period between the tasks if necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Balance/rebalancing, postural stability and weight-shifting exercises with and without visual feedback were administered using a balance platform (Biodex Medical Systems, Inc., Shirley, NY) that had been tested previously in multiple sclerosis patients [27]. Each task was trained for about 2 min, and the patients were provided with a rest period between the tasks if necessary.…”
Section: Methodsmentioning
confidence: 99%
“…A-Balance assessment procedures: 1-Biodex balance system It is an important, effective and safe tool for balance and postural stability training that can be used for treating different neurologic diseases including neuropathic patients [8] , [9]. The Biodex balance system (Biodex Crop.…”
Section: Assessment and Treatment Proceduresmentioning
confidence: 99%
“…the Biodex Balance System SD, Eftekharsadat and colleagues showed that a relatively short duration virtual reality balance training program (24 sessions) can lead to improved fall risk and postural stability performance [44].…”
Section: Usingmentioning
confidence: 99%